2(x+5)=-2(x-14)+x

Simple and best practice solution for 2(x+5)=-2(x-14)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)=-2(x-14)+x equation:



2(x+5)=-2(x-14)+x
We move all terms to the left:
2(x+5)-(-2(x-14)+x)=0
We multiply parentheses
2x-(-2(x-14)+x)+10=0
We calculate terms in parentheses: -(-2(x-14)+x), so:
-2(x-14)+x
We add all the numbers together, and all the variables
x-2(x-14)
We multiply parentheses
x-2x+28
We add all the numbers together, and all the variables
-1x+28
Back to the equation:
-(-1x+28)
We get rid of parentheses
2x+1x-28+10=0
We add all the numbers together, and all the variables
3x-18=0
We move all terms containing x to the left, all other terms to the right
3x=18
x=18/3
x=6

See similar equations:

| 61.6=4.5f-9.3+3.f | | 8s-14=6s | | 4+5(4a+4)=58+3(5a+2) | | 6x-21=15x-69 | | 5x−5=2(x+14) | | 5x−5=2(x+14) 5x-5=2x+ | | 4(3a−2)−6(2+a)=5(2a−5) | | 16v-8v+1=17 | | 3(5-2w)=10-6w | | 2w+10=-10-8w-10 | | -7-3y=-4y | | 2(3x+4)+4=9x | | 13=11c | | 7x=181 | | 11/15=a/60 | | 8f-6=-10+10f | | -0.77(c+-9)+19.1=10.63 | | 2(3x+4)=9x | | 5(1+4q)-2q=-13 | | -22=7(y+2)-3y | | 3(5x+7)=9x+39 | | 5x+18-9=20-19x+15x-2 | | -17=38-k | | 3x-5=8x-21 | | 13-6x=2+3x | | 11g=-9g+20 | | 3/4(8x-4)+3=5(2x+3) | | -9+b=4b-3 | | 9-3x-5-9x=11 | | -5x=-2x+15 | | 7(3)^(2x)=8(3)^(4x) | | 6a-10=30+a |

Equations solver categories